The Presentation of Tanggai Dance With Anna Kumari Version As A Culture Expression of Palembang Community - Sari, Pika Dian Mayang; Hartono, Hartono; Triyanto, Triyanto (Catharsis, 2021)
Tanggai Dance is one of the Malay culture products from South Sumatra. It was created based on the spirit and based on the values ​​of Palembang community. It has its own characteristics and style, as well as choreographers in the South Sumatran community, especially in the city of Palembang. One of which is the Anna Kumari version of Tanggai dance. The problem raised in this study aims to analyze the presentation of Tanggai dance as a cultural expression of the Palembang community. The approach used was a qualitative method with a case study research design. Data collection techniques included observation, interviews and document studies. The results show that the performance elements contained in Tanggai dance show several forms of behavior that lead to goodness in social life. The values which wanted to be conveyed through its moves are clearly seen in its moves. Furthermore, the presentation of Tanggai dance consists of several dance elements, namely elements of dance moves, accompaniment music, floor design, make-up, and costumes have become a unity so as to create a good art performance and definitely reflect the local culture of the Palembang community Tanggai Dance is one of the Malay culture products from South Sumatra. It was created based on the spirit and based on the values ​​of Palembang community. It has its own characteristics and style, as well as choreographers in the South Sumatran community, especially in the city of Palembang. One of which is the Anna Kumari version of Tanggai dance. The problem raised in this study aims to analyze the presentation of Tanggai dance as a cultural expression of the Palembang community. The approach used was a qualitative method with a case study research design. Data collection techniques included observation, interviews and document studies. The results show that the performance elements contained in Tanggai dance show several forms of behavior that lead to goodness in social life. The values which wanted to be conveyed through its moves are clearly seen in its moves. Furthermore, the presentation of Tanggai dance consists of several dance elements, namely elements of dance moves, accompaniment music, floor design, make-up, and costumes have become a unity so as to create a good art performance and definitely reflect the local culture of the Palembang community